Study of the weights of human heart and liver in relation with age, gender and body height - Deepika, K.; Sushma, M.; Kumar, D. Vinod (International Journal of Research in Medical Sciences, 2017)
Background: Normal weight of organ is one of the most important indicators to discern between normal and abnormal in the departments of Anatomy, Pathology also as in clinical medicine. Objective of the study was to examine the normal adult internal organ weights and their relationship with age, gender, body height. Methods: The present study included 100 autopsy cases from the mortuary of Osmania General Hospital, Hyderabad from May 2012 to September 2013. The subjects were selected as per inclusion and exclusion criteria to avoid variations arising out of pathology. The ages ranged from 10 to 60 years and out of which 29 were females and 71 were males. The organs studied were heart and liver. Results: The weight of organs with mean+standard deviation (SD) was represented for males and females respectively; heart 294+48 / 287+44gms, liver 1404 + 191/ 1283+ 169gms. Conclusions: A positive relationship was found between organ weight with age and body height in both males and females. Organ weights in males were comparatively higher than females.